Ascending pathways that mediate cholinergic modulation of lumbar motor activity. (8th August 2017) - Anglister, Lili; Cherniak, Meir; Lev‐Tov, Aharon
Abstract: Deciphering neuronal pathways that reactivate spinal central pattern generators (CPGs) and modulate the activity of spinal motoneurons in mammals in the absence of supraspinal control is important for understanding of neural control of movement and for developing novel therapeutic approaches to improve the mobility of spinal cord injury patients. Previously, we showed that the sacral and lumbar cholinergic system could potently modulate the locomotor CPGs in newborn rodents. Here, we review these and our more recent studies of sacral relay neurons with lumbar projections to the locomotor CPGs and to lumbar motoneurons and demonstrate that sacral and lumbar cholinergic components have the capacity to control the frequency of the locomotor CPGs and at the same time the motor output of the activated lumbar motoneurons during motor behavior. A model describing the suggested ascending sacro‐lumbar connectivity involved in modulation of the locomotor rhythm by sacral cholinergic components is proposed and discussed. This is an article for the  special issue XVth International Symposium on Cholinergic Mechanisms . Abstract : Sacrocaudal afferent (SCA) stimulation activates the locomotor central pattern generators (CPG) in the absence of supraspinal control. We suggest that ventral funicular (VF) projections of contra (cVFNs)‐and ipsilaterally (iVFNs) projecting sacral neurons to lumbar motoneurons (MN, blue) and CPG (red) mediate sacral control of motoneuron firing and the stepping frequency during SCA stimulation and sacral variations of neurotransmitters and neuromodulators. This is an article for the  special issue XVth International Symposium on Cholinergic Mechanisms .